Fearful and Female Narrations of Anxiety and the Boom of the Portuguese Fiction written by Women in the 1980s - Łukaszyk, Ewa (Romanica Silesiana)
The article analyses the importance of the minor genre of horror tale in the development of the Portuguese fiction written by women during the 1980s. It permitted to find a literary expression of the silenced topics, such as the fear of pregnancy and childbirth, domestic violence, prostitution. The narrations of anxiety created by such writers as Luisa Costa Gomes, Maria Ondina Braga, Lídia Jorge, Teolinda Gersão, and Hélia Correia mark a period of transition in the Portuguese culture, questioning both female and male condition. Exploration of the gender perspective leads to the utmost triumph of women that finally achieve recognition in the fields of literature and cultural criticism. At the same time, it contributes to exorcise the spectres of the patriarchal culture that became obsolete after the end of Salazarism and the Portuguese colonial empire. Key words: Portuguese women writers, tale of horror, anxiety, intimacy